TBT Effects on the Development of Intersex (Ovotestis) in Female Fresh Water Prawn Macrobrachium rosenbergii. (9th July 2014) - Peranandam, Revathi; Palanisamy, Iyapparaj; Lourdaraj, Arockia Vasanthi; Natesan, Munuswamy; Vimalananthan, Arun Prasanna; Thangaiyan, Suganya; Perumal, Anantharaman; Muthukalingan, Krishnan
Abstract : The impact of tributyltin (TBT) on the female gonad and the endocrine system in Macrobrachium rosenbergii was studied. Prawns were exposed to environmentally realistic concentrations of 10, 100, and 1000 ng/L of TBT for 6 months. Dose dependent effects were noticed in TBT exposed prawns. At 1000 ng/L TBT caused ovotestis formation (formation of male germ cells in ovary). Presence immature oocytes, fusion of developing oocytes, increase in interstitial connective tissues, and its modification into tubular like structure and abundance of spermatogonia in the ovary of TBT treated prawns. The control prawn ovary showed normal architecture of cellular organelles such as mature oocytes with type 2 yolk globules, lipid droplets, normal appearance of yolk envelop, and uniformly arranged microvilli. On the other hand, type 1 yolk globules, reduced size of microvilli, spermatogonial cells in ovary, spermatogonia with centrally located nucleus, and chromatin distribution throughout the nucleoplasm were present in the TBT treated group. Immunofluorescence staining indicated a reduction in vitellin content in ovary of TBT treated prawn. Moreover, TBT had inhibited the vitellogenesis by causing hormonal imbalance in M. rosenbergii . Thus, the present investigation demonstrates that TBT substantially affects sexual differentiation and gonadal development in M. rosenbergii .